Role of Bilingual Education on Literacy Rates in Algeria - Khaled, Ahmed (African Journal of Education and Practice, 2024)
Purpose: The aim of the study was to investigate the role of bilingual education on literacy rates in Algeria. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Bilingual education in Algeria, involving Arabic and French, has positively impacted literacy rates. Students in bilingual programs generally achieve higher literacy in both languages compared to monolingual peers. The success varies based on teaching quality and available resources, but overall, bilingual education promotes better literacy and educational outcomes. Unique Contribution to Theory, Practice and Policy: Cummins' threshold hypothesis, vygotsky's sociocultural theory & baker's theory may be used to anchor future studies on the role of bilingual education on literacy rates in Algeria. Practitioners should prioritize the development and implementation of culturally responsive bilingual education curricula tailored to the linguistic diversity present in Algeria. Policymakers should enact policies that promote the expansion and sustainability of bilingual education initiatives across Algeria.